2015
DOI: 10.4155/fmc.15.49
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Natural Products as DPP-4 Inhibitors

Abstract: Diabetes mellitus is a chronic disease affecting patients' daily life and increasing patients' risk of other complication. Dipeptidyl peptidase-4 (DPP-4) is a serine aminopeptidase, which is one of the validated targets for Type 2 diabetes therapy due to its regulatory effect of incretin hormone. Seven DPP-4 inhibitors are commercially available nowadays on the market as Type 2 diabetes drugs. They are all chemically synthesized compounds with good therapeutic effects, but long-term safety remains unknown. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 32 publications
1
44
1
1
Order By: Relevance
“…This information correlates with the obtained free-binding energy where anagliptin has the lowest binding score among other gliptin classes ( Table 3 ). While diprotin-A is a potent DPPIV inhibitor with a Ile-Pro-Ile sequence commonly used as reference compound [ 17 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This information correlates with the obtained free-binding energy where anagliptin has the lowest binding score among other gliptin classes ( Table 3 ). While diprotin-A is a potent DPPIV inhibitor with a Ile-Pro-Ile sequence commonly used as reference compound [ 17 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are more than 20 types of plant compounds reported to have DPPIV inhibitory properties and that have undergone in vitro validations. This includes compounds such as resveratrol, luteolin, apigenin, flavone, and cyanidin 3,5-diglucoside, which can be found in citrus, grapes, soybeans, and aronia berries [ 15 17 ]. Other plants species that have DPPIV inhibitory properties that have been demonstrated through in vitro studies are Urena lobata , Fagonia cretica L., Hedera nepalensis K. Koch, Senna nigricans , Commiphora mukul , Emblica officinalis , Terminalia arjuna , and Smilax china [ 18 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the discovery of DPP-IV inhibitors with new structures, especially among the secondary metabolites of plants, with higher safety, is a reliable and proven approach for discovering new hypoglycemic drugs [8]. For example, Gao et al conducted a review and reported that 63 kinds of natural flavonoids and alkaloids that inhibit DPP-IV have been found, which proves that natural products are an important source of active drugs [9].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is the fastest growing metabolic disease all over the world, identified by approximately 285 million people who have been diagnosed with DM to date, with this number predicted to increase by the year 2030. 1,2 There are some mechanisms of antidiabetic drugs and currently the category of antidiabetic drugs working on the incretin pathway is more desirable. 3 Incretin consists of a Glucose-dependent Insulinotropic Polypeptide (GIP) and Glucagon-Like Peptide-1 (GLP-1).…”
Section: Introductionmentioning
confidence: 99%